2022
DOI: 10.3390/vaccines10111802
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Influenza Vaccination among Chinese Middle School Students Based on the Health Belief Model: A Mixed-Methods Study

Abstract: Influenza vaccination rates among Chinese middle school students are low. This study aims to explore the influencing factors of vaccination among middle school students and promote vaccination. We conducted a mixed-methods study, integrating a questionnaire survey among 9145 middle school students in four cities in China and semi-structured interviews with 35 middle school students to understand their attitudes and perceptions toward vaccination based on the Health Belief Model. We found the overall vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…These findings are consistent with a recent study conducted at the end of 2022 in 14 Eastern Mediterranean region (EMR) countries, which demonstrated that half of parents in these countries were hesitant about vaccinating their children against influenza (Fadl et al, 2023). It is also in line with a study conducted among Chinese middle-school students, which found an overall vaccination rate of 38.2% in this group (Asihaer et al, 2022).…”
Section: The Main Reasons For Preferring To Vaccinate Children In Gra...supporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with a recent study conducted at the end of 2022 in 14 Eastern Mediterranean region (EMR) countries, which demonstrated that half of parents in these countries were hesitant about vaccinating their children against influenza (Fadl et al, 2023). It is also in line with a study conducted among Chinese middle-school students, which found an overall vaccination rate of 38.2% in this group (Asihaer et al, 2022).…”
Section: The Main Reasons For Preferring To Vaccinate Children In Gra...supporting
confidence: 92%
“…Most of the parental concerns raised in this study center around vaccine safety and efficacy issues. As has been previously reported, vaccine safety and potential side-effects are the main barriers to vaccination (Asihaer et al, 2022;Price et al, 2022). Interestingly, lack of trust in the Ministry of Health and in the pharmaceutical companies increased among 78% of the vaccine skeptics in our study following the COVID-19 events.…”
Section: The Main Reasons For Preferring To Vaccinate Children In Gra...supporting
confidence: 67%
See 2 more Smart Citations
“…[ 17 ] The TPB and HBM approaches have been combined in recent studies to identify health-related behaviors and intentions to receive the influenza vaccine. [ 18 19 ] So far, limited studies have investigated the intention to receive the COVID-19 vaccine. The results of a recent study on the effect of the constructs of the HBM and the TPB in predicting the intention to receive the COVID-19 vaccine have shown that these two models have good predictability in determining the intention of vaccination behavior.…”
Section: Introductionmentioning
confidence: 99%